Role of iron sucrose infusion in correction of iron deficiency anemia during pregnancy - Modh, Sanket V.; Deliwala, Kruti J.; Shah, Parul T.; Patel, Rina V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Iron deficiency anemia (IDA), is defined as decrease in the amount of red blood cells (RBCs) or hemoglobin in the blood due to insufficient iron in the body. We carried out this study to measure the efficacy of iron sucrose in iron deficiency anemia in pregnant women. Methods: In our prospective study 100 patients were included. All of them were having USG maturity between 15-34 weeks. All of them were given iron sucrose IV according to their requirements and follow-up was taken after 4 weeks by measuring Hb level. Results: Hb level improved significantly (2.1 grams) within a short duration of interval. 14% patients suffered from minor side effects. Conclusions: Iron sucrose has been found very useful for correction of iron deficiency anemia in antenatal patients.